Formal, symbolic and stylistic study of the church of Zaruma through its photogrammetric survey and rilievo - Galarza, Jorge Romero (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
All patrimonial monuments of Ecuador should have a formal record both graphic and photographic, as well as textual and informative of how they originated and what their current state is. To achieve this, it is necessary to carry out an architectural survey and rilievo. There is a big difference between these two concepts: the survey describes the physical aspects of the monument, through the taking of measurements, while the rilievo defines the building non-material aspects that help to understand its origin, geometry, shapes, symbolism and styles involved. This article reveals, through the architectural survey and rilievo, as part of the research methodology, the shape, geometry, dimensions, origin, symbolism and styles of the Main Church of Zaruma (Sanctuary of the Virgen del Carmen, located in the upper part of the province of El Oro, Ecuador, whose construction dates from 1912). This record will be very useful for the conservation and restoration of the patrimonial good in the event of an accident or deterioration due to time, and thus eventually be recovered in its original form.